Antimicrobial effects of fentanyl and bupivacaine: an in vitro study - Kesici,Sevgi (2020)
Abstract Study objective: In this study, we aimed to compare the antimicrobial effects of bupivacaine and fentanyl citrate and to reveal the impact on antimicrobial effect potential in the case of combined use. Design: In vitro prospective study. Setting: University Clinical Microbiology Laboratory. Measurements: In our study, in vitro antimicrobial effect of 0.05 mg.mL-1 fentanyl citrate, 5 mg.mL-1 bupivacaine were tested against Staphylococcus aureus American Type Culture Collection (ATCC) 29213, Pseudomonas aeruginosa ATCC 27853, Klebsiella pneumoniae ATCC 13883, Escherichia coli ATCC 25922 and Candida albicans ATCC 10231 as Group F (Fentanyl Citrate) and Group B (Bupivacaine), respectively. S. aureus ATCC 29213, P. aeruginosa ATCC 27853, Klebsiella pneumoniae ATCC 13883 and Escherichia coli ATCC 25922 were cultured onto Mueller Hinton agar (Oxoid, UK) plates and Candida albicans ATCC 10231 were cultured onto Sabouraud dextrose agar (Oxoid, UK) plates for 18-24 hours at 37 °C. Main results: In terms of inhibition zone diameters, S. Aureus ATCC 29213, P. aeruginosa ATCC 27853, and C. albicans ATCC10231 values obtained after 12 and 24 hours of incubation ​​were significantly higher in Group F than Group B (p < 0.001). In terms of inhibition zone diameters, E. coli ATCC 25922, and K. pneumomiae ATCC 13883 values obtained after 12 and 24 hours of incubation ​​were significantly higher in Group B than Group F (p < 0.001, E. coli 12ª hour p = 0.005). Conclusions: Addition of fentanyl to Local Anesthetics (LAs) is often preferred in regional anesthesia applications in today's practice owing especially to its effect on decreasing the local anesthetic dose and increasing analgesia quality and patient satisfaction. However, when the fact that fentanyl antagonized the antimicrobial effects of LAs in the studies is taken into account, it might be though that it contributes to an increase in infection complications. When the fact that fentanyl citrate which was used in our study and included hydrochloric acid and sodium hydroxide as protective agents, broadened the antimicrobial effect spectrum of LAs, had no antagonistic effect and showed a synergistic antimicrobial effect against E. Coli is considered, we are of the opinion that the addition of fentanyl to LAs would contribute significantly in preventing the increasing regional anesthesia infection complications.